Implementation of the Analytic Hierarchy Process Method for Performance-Based Rewards for Lecturers - Ruskan, Endang Lestari; Seprina, Iin; Ariani, Ardina; Indah, Dwi Rosa; Athalina, Githa (Journal of Artificial Intelligence and Software Engineering, 2025)
Rewards are carried out by the faculty as an effort to motivate lecturer performance. The obstacle is that the system has not accommodated all lecturer performance on the required indicators, the supporting files are also a problem, and the final results of many performance scores are the same, potentially due to subjective decision-making. There is no scientific formulation, no common standard, and no direct file collection system as the cause. The research method used is identifying problems and collecting data, analyzing data, designing decision support systems, and making prototypes. The research objective is to apply the analytical hierarchical process method to the application of a decision support system for determining lecturer rewards.  The contribution of research on performance-based criteria instruments applied to dynamic applications in determining indicators, so that they can be adjusted to the performance report indicators of higher education institutions. The results are in the form of lecturer performance criteria weights based on key performance. The highest lecturer performance ranking is 0.0880, the second is 0.067, and the third is 0.0663, with detailed lecturer performance scores for each criterion. These digital files can be used at any time, helping management make objective and transparent decisions.